IMPLIKASI TEORI PUNISHMENT PENDIDIKAN ISLAM DALAM PERSPEKTIF HAK ASASI MANUSIA - Zulfikar Ali Buto (Millah: Journal of Religious Studies, 2012)
This paper describes the theory of punishment in Islamic education. Punishment in education is two sides of a coin that cannot be separated. Punishment is needed as implementation of regulations that are ejected to achieve the vision and mission of education. It should be a concern that punishment in education as a means of implementation of the learning process can provide the future success of students. In this case, the punishment is not contrary to human rights as long as intended for goodness.